اختلاف الأبنية في القرآن الكريم - يونس, يونس; حسين, خديجة (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
Taght find differing formulas and buildings simslar in the words of the Koran within the context compares names and names in terms of definition and saying that the indefinite , and plural forms , and between the acts and deeds ; the expression of the past and the present tense , and the construction of the known and the construction of the unknown , and the names and deeds ; the expression palmdhara and the actor's ma,e , and source and the source , deals with the meanings and uses nuances according to the required linguisric context , and the context of the case , and trying to analyze those formulas and structures analysis linguistically accurate up to eventually secures or end semantic of isomorphism those words and similarity . And display search the views of scientists from linguists and dropped by the interpreters and Blagaan between the different destinations , opinions and attitudes between similar to those formulas and buildings and similarity , or different and contrast , all within the quranic installation and linguistic jewelers , and appropriate , and the article And ends with a conclusion find the findings of the research involved . يدرس البحث اختلاف الصيغ والأبنية المتماثلة في ألفاظ القرآن الكريم ضمن سياقها ، فيقارن بين الأسماء والأسماء من حيث التعريف والتنكير ، وصيغ الجموع ، وبين الأفعال والأفعال ؛ كالتعبير بالماضي والمضارع ، والبناء للمعلوم والبناء للمجهول ، وبين الأسماء والأفعال ؛ كالتعبير بالمضارع واسم الفاعل ، والمصدر والمصدر ، فيتناول الفروق الدقيقة بين معانيها واستعمالاتها بحسب ما يقتضيه السياق اللغوي وسياق الحال ، ويحاول أن يحلل تلك الصيغ والأبنية تحليلاً لغوياً دقيقاً ليصل في نهاية المطاف إلى المضمون أو الغاية الدلالية من تشاكل تلك الألفاظ وتماثلها . وعرض البحث آراء العلماء من لغويين ونحاة ومفسرين وبلاغيين ، فبيّن اختلاف وجهاتهم وآرائهم ومواقفهم ما بين تماثل تلك الصيغ والأبنية وتشابهها ، أو اختلافها وتباينها ، كل ذلك ضمن التركيب القرآني والسياق اللغوي ، ومقتضى الحال والمقال . وينتهي البحث بخاتمة تضمنت النتائج التي توصل إليها البحث .